Dr. Hari Narayanan shares his industrial experience - Siti Nurfarmy, Ibrahim (2019)
In a move to boost the country’s economic development, it was essential to have a competitive and highly-skilled workforce and realising its importance, the Industry & Community Network Department (ICoN) and Faculty of Industrial Management (FIM) jointly organised then ‘Professional Talk Series’ with USAINS Holding Sdn. Bhd. Director, Dr. Hari Narayanan invited as the guest speaker.